The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4028/www.scientific.net/msf.500-501.711
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Database for Fe-Cr-Mn-Ni-Ti-S-C-N System

Abstract: A database for thermodynamic information of sulfides and carbo-sulfide in steels has been developed, where the thermodynamic properties of the relevant constituting sub-system of the complex system have been assessed by the CALPHAD (Calculation of Phase Diagrams) approach. The utility of this database is demonstrated in examples of phase diagram calculations of low carbon steels and stainless steels. The calculated results are in good agreement with experimental data. The developed thermodynamic database would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The symbols in these figures represent the calculated results using CVM, and the solid lines show the Gibbs energy evaluated by fitting the CVM values using Eqs. (11) and (13). The solid lines in Fig.…”
Section: Calculated Formation Energy Kj/mol Of Atommentioning
confidence: 96%
See 1 more Smart Citation
“…The symbols in these figures represent the calculated results using CVM, and the solid lines show the Gibbs energy evaluated by fitting the CVM values using Eqs. (11) and (13). The solid lines in Fig.…”
Section: Calculated Formation Energy Kj/mol Of Atommentioning
confidence: 96%
“…Thermodynamic calculations based on the calculation of phase diagrams (CALPHAD) method have been performed to evaluate the thermodynamic properties of materials. 11,13) However, the thermodynamic parameters optimized in these calculations were obtained only using the experimental values, such as solubility products and phase equilibria, and the calculation accuracy greatly depends on the reliability of experimental values. Recently, first-principles calculations combined with a statistical thermodynamics technique have been applied to evaluate the thermodynamic stability of sulfides in IF steels at finite temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 4 C 2 S 2 precipitates when slab reheating temperature is lower than 1 100°C. Oikawa et al 15) explained by using Yamada and Niikura 28) report, that Ti 4 C 2 S 2 is stable but the activation energy for nucleation is large. Therefore the meta-stable TiS or MnS precipitates during slab reheating at around 1 200°C.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Computer simulation of precipitation in ULC Ti-stabilized steels has been done. Oikawa et al 15) reviewed the solubility products in the literatures in comparison with their thermodynamic calculation by CALPHAD. They concluded that Ti 4 C 2 S 2 is more stable than TiS and MnS.…”
Section: Introductionmentioning
confidence: 99%
“…We have already developed the thermodynamic database for Fe-Ti-C-Cr-S-Mn-Ni system. 18,19) In this study, we focused on the phase equilibria FeS-XS and MnS-XS (XS: TiS, NbS and VS) systems, because Ti, V and Nb are very strong affinity for sulfur in steels. Only a few works about phase stability and phase equilibria of sulfide mixtures in these system have been reported, 20,21) although these are essential information to determine the function of the thermodynamic database.…”
Section: Introductionmentioning
confidence: 99%